REHABILITATION AND LONG-TERM MENTAL HEALTH SUPPORT FOR SURVIVORS OF HUMAN TRAFFICKING: CLINICAL AND POLICY PERSPECTIVES - Onuh, Maria Eyiamanu; Olofin, Funke Temidayo (African Journal of Social and Behavioural Sciences, 2025)
Human trafficking inflicts enduring psychological, social, and economic harms that outlast rescue. While prevention and prosecution have advanced, the field still underinvests in the survivor’s long-term rehabilitation needs. This paper synthesizes evidence on post-trauma sequelae: PTSD, depression, anxiety, and complex trauma, and evaluates clinical and community models that support sustained recovery. We advocate for trauma-informed, culturally embedded, and survivor centered frameworks that extend beyond short-term care to encompass economic empowerment, housing stability, and social reintegration. Drawing on case illustrations from across Africa, Europe, and Asia, we identify convergent practice elements, including evidence-based therapies (e.g., CBT, EMDR), survivor-led peer networks, and context-specific supports (such as faith-based and indigenous practices). Policy analysis reveals a persistent gap between legal commitments and the provision of funded, durable services. Our central recommendation is to enshrine rehabilitation as a legal right with dedicated financing, survivor co-design in policy processes, and accountability metrics, leveraging the momentum of the 2025 Palermo context and the proposed Sicily Declaration. Rehabilitation is not ancillary to justice; it is its test, ensuring survivors are not merely rescued, but restored to safety, dignity, and opportunity.